Physicomechanical Characterization of a Novel Resin-Modified Glass Ionomer Luting Cement Functionalized with a Phosphate Functional Monomer - Rabeia J. Khalil; Abdulla M. W. Al-Shamma (International Journal of Dentistry)
Background. Resin-modified glass ionomer cements (RMGICs) are characterized by their ability to chemically bond with the tooth structure and their fluoride release, making them commonly used to retain indirect restorations. However, inferior mechanical properties and solubility (SO) are their main drawbacks compared to the most recent resin-based cement. Aim of the Study. Formulate a novel brand of experimental RMGIC (eRMGIC), based on RMGIC by incorporating 2-(methacryloxy) ethyl phosphate (2-MEP), an organophosphorus monomer with the potential to enhance mechanical properties along with low SO. Materials and Methods. eRMGICs were prepared by the inclusion of 2-MEP monomer with different weight percentages (0–40 wt%) into the RMGIC’s liquid (Fuji PLUS, GC. Corp.), then their compressive strength (CS), flexural strength (FS), film thickness (FT), setting time (ST), SO, and water sorption were examined and compared to the conventional RMGIC. Furthermore, a scanning electron microscope analyzed their surface homogeneity and integrity. Shapiro–Wilk test of normality was used to analyze data, one-way analysis of variance, Dunnett T3, and Tukey’s honest significant difference post-hoc tests. Results. After 28 days and 180 days of storage, the values of CS of the eRMGICs were significantly higher. However, after 24 hr of storage, the values were comparable to the control group. The FS results showed a double-fold increase in different concentrations of eRMGICs through all the time intervals (p<0.001) compared to conventional RMGIC. Furthermore, the inclusion of 2-MEP increased water uptake and decreased SO. The FT of experimental eRMGICs cement showed a statistically significant increase with increasing 2-MEP concentration. However, it was within the specification given by ISO 9917-1:2007. There was a decrease in the ST of eRMGICs compared to control cement; however, it was within the specification given by ISO 9917-2:2017. Conclusions. 2-MEP monomer showed encouraging results and could be used in producing new (eRMGICs) with enhanced physicomechanical properties, which can increase the longevity of cement and improve its ability to resist occlusal stresses without fracture.